Apenas questão de gênero? - Moser, Antônio (Revista eclesiástica brasileira, 2016)
Discussions on gender are livelier than ever. For this very reason, they deserve our attention. For a balanced approach, we should start with the mysteries of the body and of sexuality. Despite appearances to the contrary, the body and sexuality are dynamic realities, subject to more or less constant change. Biotechnology further highlights this possibility of changes that until recently were either spontaneous or effected through more or less conventional means. Thus, they cannot be ignored. The most important issue seems to point to a serene dialogue, through which we can dive a little deeper into the human condition. Every radicalization tends to distort reality. The search for a balance is crucial at this time when the temptation of reductionism is present in all human realities. But the balance can only be found in so far as we can value both the esse and the fieri: i.e, that which changes and that which remains.